Cerebral involvement in primary mixed cryoglobulinaemia. Issue 680 (June 1982) - Pines, Amos; Goldhammer, Ehud; Kaplinsky, Naomi; Frankl, Otto
Abstract : Primary mixed cryoglobulinaemia was diagnosed in a 65-year-old woman and confirmed on post-mortem examination. The patient had the classical findings of purpura, arthralgia, renal failure, mixed cryoglobulins in the serum and rheumatoid factor activity. The patient presented with haemolytic anaemia and later developed rectal bleeding, but the most prominent feature was an acute psychosis with electroencephalographic changes, that was attributed to the disease and responded well to corticosteroids. Primary mixed cryoglobulinaemia should be included in the differential diagnosis of central nervous system involvement in systemic connective tissue diseases. This complication should not be missed since it seems to respond well to corticosteroids and/or to plasmapheresis if diagnosed in time.